Peran return on asset dalam hubungan antara ukuran perusahaan dan tingkat bagi hasil terhadap jumlah deposito mudharabah pada bank umum syariah - Widianti, Anisa Nur; Rahman, Taufikur (Journal of Accounting and Digital Finance, 2023)
This research aims to determine the effect of company size and level of profit sharing on the amount of mudharabah deposits with return on assets as a moderating variable in Islamic commercial banks in Indonesia. This type of research is quantitative and involves a population of Islamic commercial banks registered with the Financial Services Authority (OJK). The sample for this research was determined using a purposive sampling method with criteria determined by the researcher, so 48 samples were obtained from 3 Islamic commercial banks in 2015-2020. The analysis method used is moderated regression analysis (MRA). The research results show that partially, the company size variable has a positive and significant effect on the amount of mudharabah deposits, and the profit sharing level variable has no effect on the amount of mudharabah deposits. The MRA test results show that the interaction of return on assets cannot moderate the influence of company size and the level of profit sharing on the number of mudharabah deposits.